Bangladesh, an intercultural memoir - Dil, Anwar S. (California : Intercultural Forum ; Dhaka : Adorn Publications, 2011)
Biographies of six intellectuals from Bangladesh.
Includes bibliographical references and index.
Keywords: Intellectuals -- Bangladesh -- Biography